CpG methylation is maintained in human cancer cells lacking DNMT1 - Rhee, Ina; Jair, Kam-Wing; Yen, Ray-Whay Chiu; Lengauer, Christoph; Herman, James G.; Kinzler, Kenneth W.; Vogelstein, Bert; Baylin, Stephen B.; Schuebel, Kornel E. (Nature (London), 2000)
Hypermethylation is associated with the silencing of tumour susceptibility genes in several forms of cancer 1 , 2 ; however, the mechanisms responsible for this aberrant methylation are poorly understood 3 , 4 . The prototypic DNA methyltransferase, DNMT1, has been widely assumed to be responsible for most of the methylation of the human genome, including the abnormal methylation found in cancers 5 , 6 . To test this hypothesis, we disrupted the DNMT1 gene through homologous recombination in human colorectal carcinoma cells. Here we show that cells lacking DNMT1 exhibited markedly decreased cellular DNA methyltransferase activity, but there was only a 20% decrease in overall genomic methylation. Although juxtacentromeric satellites became significantly demethylated, most of the loci that we analysed, including the tumour suppressor gene p16 INK4a , remained fully methylated and silenced. These results indicate that DNMT1 has an unsuspected degree of regional specificity in human cells and that methylating activities other than DNMT1 can maintain the methylation of most of the genome.